Ethiopia’s Burgeoning Democratic Transition: New Glamour or New Statesmanship Gimmicks? - Abdi, Ali Ahmed (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
Following the amounting accusation of autocracy, the heritage of exclusionary rulership with an underlying ethnic undertone that confined the parameters of political power finally yielded nearly three years of unemployed youth-led street protests initially in Oromia region and later spread all over the country, demanding for political reform and socio-economic improvements. All these paved the way for PM Abiy Ahmed on April 2nd, 2018 in what seemed to be a transition in the form of a “play-within-a-play”. In this article, I offer an account that explains the image of Ethiopia’s democratic transition in 2018, undeniably using my own physical experience and observations as an academic and a humanitarian practitioner owing to my more than 15 years of stay in the country where I have often been close to the decision-making tables in Addis Ababa as well as in the Somali region. Of course, I will also use all other seminally relevant information helpful to draw an explanation to the interminable socio-political and economic transformation in Ethiopia.